Normative Legitimität von Recht, Moral und Menschenrechten im Lichte der positivistischen Trennungsthese - Blöchlinger, Moritz (Schriften zur Rechtstheorie, 2022)
»Normative Legitimacy of Law, Morality and Human Rights in the Light of the Positivist Separation Thesis«: On the basis of the positivist separation thesis, this study provides in-depth answers to the question of the manner in which state law, international law, morality and human rights can be considered normatively legitimate and what this legitimacy means in each case. The focus is not on specific substantive criteria of legitimacy, such as democratic procedures or certain notions of justice. Rather, the question is more fundamentally about the formal conditions of legitimacy.